Amazon Go, surveillance capitalism, and the ideology of convenience. Issue 2 (12th May 2021) - Huberman, Jenny
Abstract : How does convenience operate not just as a highly coveted consumer good that stands to mitigate the demands of life in a fast‐paced society but also as an ideology that is integral to new forms of capital accumulation, domination, and extraction? Taking Shoshana Zuboff's work on surveillance capitalism as a departure point, in this article I explore this question by focusing on one of Amazon's newest business initiatives, Amazon Go. Launched in 2018, the initiative has involved opening twenty‐six stores intended to enhance customer convenience by weaving "machine learning, computer vision, and AI into the very fabric of the store, " so customers "never have to wait in line." Drawing on a range of data, including promotional videos, marketing reports, interviews with the designers of the initiative, and customer comments, I show how convenience operates not just as a coveted consumer product but also as an ideology that is central to Amazon's abilities to exploit the behavioral surplus of its customers and legitimate new forms of capital accumulation and extraction. By interrogating how convenience functions in this capacity, this article seeks further understandings of the convenience economy while also returning to a long‐standing question within economic anthropology: What role do ideologies play in sustaining and perpetuating exploitative economic systems?